Social desirability scales as indicators of self-enhancement and impression management - Parmač Kovačić, Maja (Array, 2014)
This paper presents two studies testing Paulhus' (2002) assumption that unconscious self- enhancement and conscious impression management represent separate processes of socially desirable responding (SDR) that can be observed within two content domains (egoistic and moralistic bias). In Study 1, we devised egoistic and moralistic SDR scales intended to measure self-enhancement in honest responding and impression management under demands for positive self-presentation. In Study 2, we correlated scores on these scales with external indicators of unconscious and conscious bias. In honest responding, both SDR scales most strongly correlated with self-enhancement indicators, whereas under demands for positive self-presentation they correlated more strongly with external measures of impression management.